Geothermal resource exploration in South America using an innovative GIS-based approach: A case study in Ecuador. (February 2023) - Jara-Alvear, Jose; De Wilde, Thomas; Asimbaya, Danilo; Urquizo, Matilde; Ibarra, Danilo; Graw, Valerie; Guzmán, Pablo
Abstract: Integrating geothermal energy contributes to a sustainable energy transition in South American countries. Geothermal energy is a non-variable and renewable resource that can be used for baseload power generation to reduce the overdependence on fossil fuel and hydropower plants. There is a vast and untapped geothermal potential in South America. Nevertheless, multiple barriers, including lack of geological, hydrogeochemical and geophysical background and outdated regional studies have blocked the development as it should be. Thus, this study aims to update and identify promising areas for further geothermal exploration through a favourability map implemented in a GIS-based model for Ecuador as a case study. The results show that approximately half (49.2%) of the national territory of Ecuador has promising areas to explore and develop geothermal systems along the Andean and South-west coast. New zones were identified, which contribute to increasing the national inventories of geothermal energy. Also, the Northern Amazon region presents mature oil fields and reservoirs close to their productive life. Thus, geothermal energy systems may help transition the petroleum industry into a clean energy provider. This research contributes to the needed improvement of existing geothermal resource inventories. The robustness of the proposed GIS-based model has been tested. Thus, it allows the analysis and combination of available open geodata in an effective, low-cost method, and even under a scenario of scarce data availability, to support decision-makers, researchers, or stakeholders, and guide geothermal exploration programs at a national level. Highlights: A geothermal resource exploration is done at the regional level, at low cost, and with data scarcity using a GIS-based model. Validation of the GIS-based model is done through a robustness analysis to allow its transferability to other countries. Half of Ecuador's territory holds the most promising areas for further geothermal exploration. New promising areas for geothermal energy have been identified in the central Andes, and west coast of Ecuador.